354 Differential Attainment in Surgical Training. (4th May 2021) - Vinnicombe, Z; Little, M; Super, J
Abstract: Introduction: Differential attainment (DA), according to the General Medical Council (GMC), is the gap between attainment levels in different groups. Attainment measures should cover aspects that include academic performance and career progression. Two such areas in surgical training are the MRCS examinations and ARCPs, both of which are required for progression in a career in surgery. Our aim was to investigation whether socio-economic background was a significant factor for progression in surgical training. Method: Data from the GMC for Core Surgical Trainees (CSTs) taking the MRCS examination between 2016 and 2019 and CST ARCP outcomes between 2017 and 2019 were obtained. Socio-economic background was assessed using the Index of Multiple Deprivation (IMD). ARCP and MRCS outcomes were assessed against IMD. Results: Trainees from IMD Q1&2 (most deprived) had a significantly higher (p < 0.01) mean number of attempts (1.86) to pass MRCS examinations than trainees from IMD Q4&5 (least deprived) (1.54). IMD Q1&2 were significantly more likely to obtain unsatisfactory outcomes (24.4%) than trainees from IMD Q4&5 (14.2%) (p < 0.05). Conclusions: There is clear evidence that differential attainment exists within Core Surgical Training. The reasons for this are likely to be complex and more work is needed to further investigate the relationship.